Mechanically Powered Negative Pressure Dressing Enhances Surgical Incision Cosmesis: A Randomized Trial - Brian Williams, MD; Abhinav Gupta, MD; Jordan Martucci, MD; Aubrey Swinford, MD; Kyle G. Cologne, MD; Sarah E. Koller, MD; Joongho Shin, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Cosmetic appearance of incisions remains one of the most important aspects of the patient recovery experience. Despite advances in surgery, scar prevention is the gold standard in improved results. Closed-incision negative pressure wound therapy has shown promise in decreasing surgical site infection and healing time. This study aimed to assess outcomes of primarily closed surgical incisions with mechanically powered negative pressure dressings (MP-NPDs) compared with standard dressings. Methods:. This study was a single-center, within-subjects, randomized controlled trial, in which each patient served as both the control and experimental arms. Laparoscopic/robotic port site incisions were randomized to control dressing or MP-NPD. Primary outcomes were cosmetic results at first clinic visit by blinded physicians and nonphysician observers. Results:. Forty patients with a total of 80 incisions were included in the analysis. The average scores for scar spread, erythema, dyspigmentation, scar hypertrophy, and overall impression were lower for the MP-NPD wounds. The only individual variable of the Scar Cosmesis Assessment Rating scale, in which there was no difference noted between the 2 groups, was the presence of suture marks. The average total Scar Cosmesis Assessment Rating score was significantly lower (more favorable) for the MP-NPD wounds compared with the control wounds (3.39 ± 3.18 versus 4.79 ± 3.18, respectively; P < 0.001). Conclusions:. The use of closed-incision negative pressure wound therapy with the application of a novel MP-NPD over surgical incisions resulted in clinical and statistically significant improvement in scar cosmesis in the early/intermediate postoperative period according to both physician and nonphysician observers.